2010
DOI: 10.1002/bmc.1510
|View full text |Cite
|
Sign up to set email alerts
|

Rapid ultraperformance liquid chromatography–tandem mass spectrometry method for quantification of oxcarbazepine and its metabolite in human plasma

Abstract: A rapid and sensitive ultraperformance liquid chromatography tandem mass spectrometry assay was developed for the simultaneous analysis of oxcarbazepine and its main metabolite in human plasma. The assay involves a simple solid-phase extraction procedure of 0.3 mL of human plasma and analysis was performed on a triple-quadrupole tandem mass spectrometer in multiple reaction monitoring mode via electrospray ionization. Separation was achieved on an Acquity UPLC™ BEH C₁₈ column (50 × 2.1 mm, i.d., 1.7 µm) with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The plasma concentrations of oxcarbazepine decreased slowly in the first hours after sampling, with elimination half‐lives from 1 to 5 h in studies with healthy volunteers treated with single or multiple doses of oxcarbazepine . The oxcarbazepine elimination half‐life (t 1/2 ) of 5.4 h obtained in the present study is also in agreement with the values reported by Bhatt et al of 8.3 ± 3.6 h in healthy volunteers treated with a single dose of 600 mg oxcarbazepine.…”
Section: Discussionsupporting
confidence: 91%
“…The plasma concentrations of oxcarbazepine decreased slowly in the first hours after sampling, with elimination half‐lives from 1 to 5 h in studies with healthy volunteers treated with single or multiple doses of oxcarbazepine . The oxcarbazepine elimination half‐life (t 1/2 ) of 5.4 h obtained in the present study is also in agreement with the values reported by Bhatt et al of 8.3 ± 3.6 h in healthy volunteers treated with a single dose of 600 mg oxcarbazepine.…”
Section: Discussionsupporting
confidence: 91%
“…TDM depends upon reliable analytical methods for the determination of plasma/serum levels of drugs and their metabolites. Several HPLC methods coupled to ultraviolet (HPLC‐UV) (Fortuna, Sousa, Alves, Falcao, & Soares‐da‐Silva, ; Greiner & Haen, ; Hunek, Burgyan, & Wang, ; Kimiskidis et al, ; Serralheiro, Alves, Fortuna, Rocha, & Falcao, ) or mass spectrometry (HPLC–MS/MS) (Bhatt, Shah, & Shivprakash, ; de Sousa Maia et al, ; Maurer, Kratzsch, Weber, Peters, & Kraeme, ; Paglia, D'Apolito, Garofalo, Scarano, & Corso, ; Subramanian, Birnbaum, & Remmel, ; Yin et al, ) detection have been developed for the determination of licarbazepine in human serum either alone or simultaneously with other antiepileptic drugs. In general, MS‐based methods are characterized by significant advantages such high sensitivity, fast analysis times and limited sample volumes; however, they often involve expensive and sophisticated equipment requiring specially trained personnel.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in addition to its antiepileptic action, oxcarbazepine has been also used in the treatment of bipolar disorders as monotherapy or as adjunctive treatment of affective disorders (Misdrahi et al, ). A number of studies have considered, to date, the interference of antiepileptic (Bhatt et al, ; Contin et al, ; Fortuna et al, ; Greiner‐Sosanko, Giannoutsos, Lower, Virji, & Krasowski, ; Heideloff, Bunch, & Wang, ; Maurer et al, ; Subramanian et al, ; Yin et al, ) or other commonly used drugs (Fortuna et al, ; Greiner‐Sosanko et al, ) with licarbazepine quantification. Nevertheless, only one study has, thus far, investigated the interference of licarbazepine with antidepressant or antiphsychotic drugs which may be co‐prescribed with oxcarbazepine (Greiner & Haen, ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of mass spectrometry (MS) improves the selectivity during detection and enables detection of ions formed from small molecules. However, most of the reported methods have been restricted to a single drug and its metabolites, or they required time‐consuming solid‐phase extraction in the pretreatment (Breton et al ., ; Mendu and Soldin, ; Bhatt et al ., ). No simple and rapid method for routine TDM has been reported to date.…”
Section: Introductionmentioning
confidence: 97%